The full-genome characterization and phylogenetic analysis of bovine herpesvirus type 1.2 isolated in China - Guo, Weiqiang; Xie, Jia; Liu, Jingyi; Chen, Hongjun; Jung, Yong-Sam (Frontiers in Microbiology, 2022)
Bovine herpesvirus type 1 (BHV-1) causes bovine respiratory disease that poses significant threat to the cattle industry. The prevalence of BHV-1 has recently increased in China. However, the lack of information about the prevalent isolates limits the control of the disease. In this study, a novel strain of BHV-1 was isolated from nasal swabs of Holstein cows in 2020 of China, designated as BHV SHJS. The genome of BHV strain SHJS is 135, 102 bp in length and highly similar to strain SP1777 (KM258883.1) with an identity of 99.64 %. Mutations, insertions, or deletions mainly occur in UL27, UL44 and US8 etc, relative to the different genomic coordinates. Phylogenetic tree of UL44 (gC) showed that BHV strain SHJS belong to BHV-1.2b cluster. The result showed that the strain had a different evolutionary origin from those prevalent in China. This study will enrich our knowledge regarding BHV outbreak strains in China and contribute to the prevention and pathogenic studies of BHV-1.2.